Stress biomarkers as predictors of transition to psychosis in at-risk mental states: Roles for cortisol, prolactin and albumin - Labad, Javier; Stojanovic-Pérez, Alexander; Montalvo, Itziar; Solé, Montse; Cabezas, Ángel; Ortega, Laura; Moreno, Irene; Vilella, Elisabet; Martorell, Lourdes; Reynolds, Rebecca M.; Gutiérrez-Zotes, Alfonso (Journal of psychiatric research, 2015)
Stress and inflammation are thought to play a role in the risk of developing a psychotic disorder. We aimed to identify stress-related biomarkers for psychosis transition in help-seeking individuals with an at-risk mental state (ARMS). We studied 39 ARMS subjects who were attending an Early Intervention Service. We included a control group of 44 healthy subjects (HS) matched by sex and age. Stressful life events and perceived stress were assessed. Stress-related biomarkers were determined in serum (cortisol, prolactin, C-reactive protein and albumin), plasma (fibrinogen) or saliva (morning cortisol, cortisol awakening response). All ARMS were followed-up at our Unit for at least one year. We divided the ARMS group into two subgroups based on the development of a psychotic disorder (ARMS-P, N = 10) or not (ARMS-NP, N = 29). ARMS-P reported more stressful life events and perceived stress than HS and ARMS-NP groups. In relation to baseline stress biomarkers, ARMS-P subjects had increased prolactin and lower albumin levels in serum, when compared to ARMS-NP and HS groups. These results did not change when repeated in a subsample of antipsychotic-naïve ARMS subjects. We also found significant differences between groups in the cortisol secretion after awakening. In a multinomial logistic regression adjusting for age, sex and life stress, prolactin was a predictor of psychosis transition whereas albumin levels had a protective effect. Our study underscores the role of stress and stress-related biomarkers (cortisol awakening response, prolactin and albumin) in the pathogenesis of psychosis. •Baseline stress-related biomarkers predict psychosis in at-risk mental states (ARMS).•Increased prolactin levels were associated with the risk of developing a psychotic disorder.•Albumin plasma levels had a protective effect on conversion to psychosis.•ARMS subjects with a psychosis transition had an enhanced cortisol awakening response.